Asymmetric relationships among financial sector development, corruption, foreign direct investment, and economic growth in sub-Saharan Africa - Emmanuel Asafo-Adjei; Peterson Owusu Junior; Anokye M. Adam; Clement Lamboi Arthur; Ebenezer Boateng; Kwadwo Ankomah (Cogent Economics & Finance, 2023)
Prior studies on the relationship between FDI and growth have generally concentrated on mean effects, or average growth benefits. It seems improbable that the majority of sub-Saharan economies will have similar "average" economic growth, hence the emphasis on mean effects in particular falls short. All other drivers can be seen to have an impact based on the uneven growth rates of these economies. The current study brings new evidence about the asymmetric relationship between foreign direct investment (FDI) and economic growth amidst financial sector development (FSD) and corruption covering a sample period of 2002 to 2020 for 48 sub-Saharan economies. For this reason, the instrumental variables panel quantile regression technique is employed to achieve the purpose of the study. The study finds that FDI inflows have a significant positive relationship with economic growth for economies with low growth (less than 50% quantile) but negative at high growth levels (at quantiles 50% and beyond). Also, control of corruption significantly interacts negatively with FDI and GDP per capita irrespective of the GDP levels, whereas FSD significantly positively interacts with FDI to contribute to economic growth at various growth levels. Findings from the study imply that FSD promotes economic growth in sub-Saharan Africa at diverse growth levels. On the other hand, the interacting effect of control of corruption is inimical to FDI-growth nexus at all growth levels. It is pertinent that efforts are made by financial policymakers in sub-Saharan Africa to improve the local financial sector conditions to recuperate the economic advances from FDI.
Keywords: 330; Dependency; Domestic credit to private sector; Financial development; Gross domestic product; Heterogeneity; Panel quantile regression